Concept of Ayurgenomics in Context to Nutrigenomics - Soni Kapil,; Laxmita Gaiju, (International Journal of Ayurveda and Pharma Research, 2022)
Nutrigenomics is an emerging branch of science that creates foundation of the relationship between nutrients from diets and their effects on expression of genomes. It also encompasses the heterogenous response of gene to different nutrients, dietary components and developing nutraceuticals under the heading of nutrigenetics. Exploring the aspects of nutrigenomics has been conceptualised to develop the approaches for the determination of the etiology of different physiological conditions, pathological conditions alongside the management of different morbidities by application of the dietics and also prevention of certain possible gene expression causing morbid conditions. All these facts that diet plays in determination of health or disease have already been mentioned in the ancient times by the scholars of Ayurveda. Ayurgenomics in other side includes of classical facts that has been mentioned in the Ayurvedic classic texts which clearly mentions that the Aahar determines the state of health and diseased conditions in an individual. It determines the individuality in the requirement of the nutritional sources in all different individual is different and unique. When the nutrition for the individual is personalised determining the Prakriti (constitution) of the individual, this will ensure maintaining the health and resolving the diseases in the subject. Also different forms of incompatible combinations of Aahar have also been mentioned in Ayurveda and their different levels of effects in different individual have been described under the topic of Virruddhaahar. Analytical study of these subjects together could be manifested in the management of different pathological conditions or even for the prevention of the disease condition in the field of disease management